Linking Exercise Intention to Exercise Action: The Moderating Role of Self-Efficacy - Hou, Bin; Li, Linqian; Zheng, Lei; Qi, Yating; Zhou, Song (Frontiers in Psychology, 2022)
Physical exercise benefits both physical and psychological health among college students. Thus, how to promote and maintaining physical exercise becomes increasingly important for them. Our research adopted the Health Action Process Approach (HAPA) model to understand the exercise intention-action gap, and determine the promoting role of self-efficacy. We recruited 242 students from a university in China, who were informed to complete a six-wave survey. Our results indicated that exercise intention was positively related to both coping and action planning, which further results in exercise action. Such mediation effects varied under conditions of self-efficacy. For college students with high self-efficacy, there were stronger relationships between intention and planning, and between planning and action. Our research suggested the time-lagged mediation effects of planning in the relationship between intention and action. Further, we find that the promoting effects of self-efficacy in health-promotion changes shed light to develop strategies for college students.